AIZGAVIEŅS AND МАСЛЕНИЦА ( SHROVETIDE ) IN LATGALE : TRADICIONS OF LATGALIAN AND OLD-BELIEVERS - Koroļova, Jeļena; Ūdre, Sandra (Via Latgalica, 2013)
The collective memory better than the individual memory holds the form (actions, words, formulas, scripts) than the matter (why it’s done). That is also true about aizgavieņs and масленица (Shrovetide), the archaic seasonal-rite feasts celebrated in Latgale. Nevertheless in the survey made by Rēzekne University College within the framework of ESF project “Linguo-Cultural and Socio-Economic Aspects of Territorial Identity in the Development of the Region of Latgale” (tilra.ru.lv) 1308 respondents (out of 1959, including 102 questionnaires in Russian) acknowledged Shrovetide as one of Latgalian identity features. In the list of 466 items (well-known people, places, traditions, realias, fi xed phrases, words etc) it holds 67th place. The aim of the work is to describe in comparative aspect the Latgalian and the Old- Believers’ traditions of the time before fasting, stressing syncretism of pagan, Christian (denominationally different) and ideological elements, using linguo-cultural approach. For the work published and unpublished materials of Latgalian folklore as well as the materials of Daugavpils University expedition about Old Believers and for comparing some materials of ethnographic studies in Pskov district (Мехнецов 2002; Прауст 2009) have been used. For all the Indo-European peoples, as they are agricultural people, the rhythm of life and work depends on the solar cycle; for an archaic human being it is the only system of reference frame. Acts of nature determine the quality of life all the year – the harvest should supply food till the next season. Preparing for the new agricultural season (the end of winter) is archaic New Year in modern understanding (Пропп 1995: 33), for archaic people to whom calendar doesn’t exist. Both at Shrovetide and at New Year’s Eve people read fortune about future spouse and the popular beliefs are very similar. Both Latgalians and Old Believers have popular beliefs connected with land tending at New Year eve fortunetelling, for example: at New Year’s Eve they went to crossroads to sow fl ax and later waited that at dream the future husband would come to tend land for flax. Other position: Масленица is the amount of summer solstice and other spring rituals (Клейн 2004: 312). For Slavic people the fertility of land is closely connected with prosperity and mercifulness of its inhabitants. Ritual food and wine is put for the shades, they are asked to come to fire, and they are asked for forgiveness, the graves are visited. For Catholics this time is not the time of commemorating the dead, so Latgalians encourage the growth of the most important for their culture plant – flax – with ritual actions. Most popular beliefs put down in Latgale are related to riding down a hill in a sledge as far as possible or with a horse travel far from home – so the flax grow as long as those ridings. In Latgale not only traditional sledges, but also ladonkys and skretels are used for riding. Ladonkys is a sleigh cut from ice with a hole for a rope and a groove for sitting, where a blanket is put. Seretels is a stake put in low wet place (to freeze in winter) in autumn to which at Shrovetide a pole is attached so the sleigh could be tied to it and spins round. The parade of disguised develop the topic of fertility in a social context. For Shrovetide a superfluity is typical both in entertainment and in food, but the timeline is strictly kept up. Latgalians prepare mainly meet dishes. They eat nine or twelve times and each time they eat meet. Slavic people celebrate Shrovetide for a week, they taste fat dishes, but they don’t eat meet at that time. The symbol of the Shrovetide menu is a pancake, which is the most ancient flour dish and the dish of Cult of the dead, it symbolizes prosperity and satiety. The Shrovetide menu of Latgalians is also unimaginable without it. Catholic fasting starts exactly at midnight of Ash Wednesday when merry-making and easy- time stops. Old-Believers fasting starts on Monday. Archaic ceremony is getting forms of mass events, since even in the conditions of Soviet ideology beginning since 50s of the 20th century, масленица has been celebrated as a farewell to winter with well-known for children Grandfather Frost (Дед Мороз) and The Snow Maiden(Снегурочка), with singing songs, playing games, horse races and horse- riding. Since 90s of 20th century all national groups living in Latgale have been integrated in the celebration of Shrovetide. In 1995 the public disguise event Daugavpils International Masque Festival has been launched where not only local national groups, but also guests from abroad demonstrate their national traditions. The celebration of Shrovetide has got the forms of mass cultural events emphasising its connection to certain place or specific aim of the initiators, for example: the songfest “Aizgavēnī cīmā braucam” (“In Shrovetide we vent on a visit”) of quires and folk companies in Vabole, the meeting of amateur theatres “Aizgavēņa grīztovōs“ (“In the gin-pole of Shrovetide”) in Līvāni (2011), the meeting of performance companies of Rēzekne Schools “Griešanās Aizgavēnī“ (“Rotation in Shrovetide”), “Aizgavieni” (“Shrovetide”) in Baltinava Secondary School; at the same time the restriction of social tradition as well as professional accomplishment can be traced.